Cystic Angiomatosis of the Bone Appearing as Intrathoracic Lung Masses - Tomas Pulido-Zamudio; William Orr; Morley Lertzman (Canadian Respiratory Journal)
A rare case of cystic angiomatosis of the bone (CAB) manifesting as bilateral intrathoracic masses is described. In 1996, a 47-year-old woman was referred to the chest clinic at St Boniface Hospital for evaluation of chronic cough, and her chest radiograph showed large, bilateral pleural-based intrathoracic masses. Ten years before, she had been diagnosed with CAB following bone biopsies of her hip and knee. Computed tomography revealed two chest wall masses with internal septations of bone. CAB is a rare, multicentric disease characterized by involvement of the vascular and lymphatic systems, producing diffuse cystic lesions in the skeleton. Although the ribs are frequently involved, the presentation with intrathoracic masses is uncommon.